PRIMARY SCHOOL INCLUSIVE EDUCATION: PEDAGOGICAL STRATEGIES FOR COMPLETING ACADEMIC TASKS AND DEVELOPING ACADEMIC VALUES IN EFL CLASSROOMS (SCIENCE TIME JOURNAL, 2026)
This article considers practical ways of teaching English in inclusive primary school classrooms. Special attention is given to how teachers can help pupils with special educational needs complete academic tasks and at the same time develop important learning values such as responsibility, persistence and respect for others. The study is based on classroom observations and analysis of teaching experience in Uzbek schools, as well as on current approaches including differentiated instruction and Universal Design for Learning (UDL). The results show that when tasks are adapted, supported visually and organised through cooperation, pupils become more engaged and confident in their learning. Inclusive strategies not only support children with learning difficulties but also improve the overall classroom environment. At the same time, a number of challenges remain, including limited resources, lack of specialised materials and insufficient teacher training. The article suggests several practical steps that can help improve inclusive teaching in primary schools and make language learning more accessible for all learners.